2016
DOI: 10.1016/j.mod.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-rich membrane microdomains modulate Wnt/β-catenin morphogen gradient during Xenopus development

Abstract: Wnt/β-catenin has been described as crucial for dorsal-ventral and antero-posterior patterning, playing multiple roles at different stages of development. Cholesterol-rich membrane microdomains (CRMMs), cholesterol- and sphingolipid-enriched domains of the plasma membrane, are known as platforms for signaling pathways. Although we have demonstrated the importance of the CRMMs for head development, how they participate in prechordal plate formation and embryo axis patterning remains an open question. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…6a, open arrowheads ). Because GPI-anchored proteins localize to lipid rafts 40 , we applied methyl-β-cyclodextrin (MβCD) to Xenopus embryos to disrupt lipid rafts by removing cholesterol 41 . The data showed that MβCD treatment reduced both N- sulfo-rich and N- acetyl-rich HS clusters in a dose-dependent manner (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6a, open arrowheads ). Because GPI-anchored proteins localize to lipid rafts 40 , we applied methyl-β-cyclodextrin (MβCD) to Xenopus embryos to disrupt lipid rafts by removing cholesterol 41 . The data showed that MβCD treatment reduced both N- sulfo-rich and N- acetyl-rich HS clusters in a dose-dependent manner (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…iii) the suppression of resveratrol-induced activation of kinase-dependent signaling pathways (c-Jun NH2-terminal kinase/ERK/Akt) and caspase-dependent apoptosis in colon cancer cells (Colin et al, 2011); iv) the activation of Wnt/β-catenin pathway which plays multiple roles at different stages of development of Xenopus laevis (Reis et al, 2016); v) the activation of protein kinase A and tyrosine kinase resulting in protein phosphorylation and sperm capacitation (Osheroff, 1999;Visconti et al, 1999); vi) the enhancement of antigen receptor-mediated intracellular calcium release in Ramos B cells (Awasthi-Kalia et al, 2001), and its inhibition in Jurkat T cells (Kabouridis et al, 2000); vii) the enhancement of signaling pathways associated with β1-adrenergic receptors resulting in compartmentalized cyclic adenosine monophosphate (cAMP) response in cardiac monocytes (Agarwal et al, 2011); viii) the suppression of cAMP-dependent protein kinase (PKA) modulation of voltage-gated potassium channel (Kv) current in rat mesenteric artery smooth muscle cells (Brignell et al, 2015); ix) the suppression of signaling pathways associated with chemokine receptor (CCR5), leading to the inhibition of calcium release and abrogation of inhibition of forskolin-stimulated cAMP accumulation in Chinese hamster ovary cells and human embryonic kidney cells (Cardaba et al, 2008), x) the suppression of insulin-stimulated Akt phosphorylation in mice hepatocytes (Key et al, 2017); xi) other signaling pathways may also be involved. Additionally, CD-induced extraction of other membrane components (PLs or proteins) may affect several signal transduction pathways.…”
Section: The Effects Of Cyclodextrins On Signal Transduction Pathwaysmentioning
confidence: 99%
“…Thus, β-catenin knockdown inhibited the phenotype caused by cholesterol depletion. (Reis et al, 2016). In order to test this we performed the following elegant experiment: we created an ectopic Wnt morphogen field by injecting Wnt8 together with β-galactosidase so we could trace the evolution of the field.…”
Section: Prechordal Plate and Anterior Neural Plate Let's Form The Headmentioning
confidence: 99%
“…Next we recognized that this ectopic field was able to displace the Otx2 expression domain a little bit away from its normal site. Remarkably, when MβCD was injected in the blastocoel of embryos that had been previously injected with Wnt8 and β-galactosidase, the Otx2 expression domain was displaced much further from Wnt source or, in some cases, completely abolished (Reis et al, 2016).…”
Section: Prechordal Plate and Anterior Neural Plate Let's Form The Headmentioning
confidence: 99%